2013
DOI: 10.1177/1098612x12470652
|View full text |Cite
|
Sign up to set email alerts
|

Feline degenerative joint disease: a genomic and proteomic approach

Abstract: The underlying disease mechanisms for feline degenerative joint disease (DJD) are mostly unidentified. Today, most of what is published on mammalian arthritis is based on human clinical findings or on mammalian models of human arthritis. However, DJD is a common occurrence in the millions of domestic felines worldwide. To get a better understanding of the changes in biological pathways that are associated with feline DJD, this study employed a custom-designed feline GeneChip, and the institution's unique acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Another possible explanation for the concurrency could be shared etiology of CKD and DJD. The cause of primary DJD in cats is not currently known, although inflammatory and immune-mediated etiologies have been suggested,38 and immune dysfunction has been seen in association with DJD in a genomic/proteomic study 39. A previous study of DJD in cats revealed an increase in the prevalence of azotemia, but this significant association was no longer statistically significant when controlled for age 10.…”
Section: Discussionmentioning
confidence: 97%
“…Another possible explanation for the concurrency could be shared etiology of CKD and DJD. The cause of primary DJD in cats is not currently known, although inflammatory and immune-mediated etiologies have been suggested,38 and immune dysfunction has been seen in association with DJD in a genomic/proteomic study 39. A previous study of DJD in cats revealed an increase in the prevalence of azotemia, but this significant association was no longer statistically significant when controlled for age 10.…”
Section: Discussionmentioning
confidence: 97%
“…As there were not age matched control samples available for analysis, this finding may be more strongly associated with age than with DJD or pain, however pain score category appeared to explain more of the increase in IL-8 concentration than age in our model. A recent study has suggested that DJD in cats is associated with changes in genetic and proteomic profiles more extreme than simple aging (Gao et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Suggestions from a recent proteomic and genomic study of cats with DJD found that gene expression differences between cats with DJD and an age-matched group of cats without DJD were particularly evident in three main pathways: immune function, apoptosis, and oxidative phosphorylation (Gao et al, 2013). Proteomic analysis of serum found that cats with DJD had an increase in components of the complement system as well as down-regulation of the complement system regulator clusterin (Gao et al, 2013). Up-regulation of the complement system can lead to activation of macrophages and inflammatory cytokine secretion (Haseeb and Haqqi, 2013), and cartilage matrix components can activate complement (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was hybridised to the Affymetrix Feline GeneChip 1.0 ST Array microarray. Feline mRNA expression has previously been analysed by cross-hybridisation to human microarrays, as feline genes have generally >85% similarity to their human counterparts (Collison et al, 2012;Dowling and Bienzle, 2005), and whole blood expression profiling has been performed using a custom cDNA array (Gao et al, 2013). To our knowledge, this is only the first report of feline monocyte transcriptional profiling, using a feline-specific microarray.…”
Section: Feline Peripheral Blood Monocytes Exhibit a Monocyte-enrichementioning
confidence: 99%